Feeding practices and other factors associated with faecal consistency and the frequencies of vomiting and diarrhoea in captive tigers (Panthera tigris) - S.L. Lefebvre; H.M. Wallett; E.S. Dierenfeld; K.M. Whitehouse-Tedd (Journal of Applied Animal Nutrition)
Gastrointestinal (GI) health is important to the welfare of captive tigers, and diet is considered a likely influencing factor. A survey was performed to collect information on GI health indicators and diet of tigers housed in zoological facilities across the globe. Completed surveys were received for one tiger from each of 32 facilities. Three (9%) tigers were reported as being diagnosed as having current GI disease; 24 (75%) had ideal (soft with shape) faeces ‘often’ to ‘always’ during the four weeks before survey completion. Potential associations between current GI disease and other variables could not be explored because of the low disease prevalence. Commercial raw meat diets were the most commonly fed diet type, and the most common food source was horse. Upon multivariate analysis, including country as a covariate, the odds and frequency of vomiting during the previous six months increased with the frequency of feeding muscle meat and chicken, and decreased as the frequency of feeding long bones increased. The odds and frequency of diarrhoea over the previous six months increased with the frequency of feeding beef and muscle meat; and the frequency of liquid faeces in the previous four weeks increased with oral antimicrobial treatment and increasing frequency of feeding beef. Although limited by the small sample size, these findings characterised the nutritional care that captive tigers currently receive and provided preliminary insight into dietary associations with indicators of GI health. The findings support the need to consider species-specific dietary adaptations and for further investigations into the health impact of diet in captive tigers.